Kinematic, finite strain and vorticity analysis of the Sisters Shear Zone, Stewart Island, New Zealand. (April 2015) - Ring, Uwe; Bernet, Matthias; Tulloch, Andy
Abstract: The Sisters Shear Zone (SSZ) on Stewart Island, New Zealand, is a greenschist-facies extensional shear zone active prior to and possibly during the development of the Pacific–Antarctica spreading ridge at ∼76 Ma. We report quantitative kinematic and rotation data as well as apatite fission-track (AFT) ages from the SSZ. Early kinematic indicators associated with the NNE-trending stretching lineation formed under upper greenschist-facies metamorphism and show alternating top-to-the-NNW and top-to-the-SSE senses of shear. During progressive exhumation lowermost greenschist-facies and brittle-ductile kinematic indicators depict a more uniform top-to-the-SSE sense of shear in the topmost SSZ just below the detachment plane. Deformed metagranites in the SSZ allow the reconstruction of deformation and flow parameters. The mean kinematic vorticity number (Wm ) ranges from 0.10 to 0.89; smaller numbers prevail in the deeper parts of the shear zone with a higher degree of simple shear deformation in the upper parts of the shear zone (deeper and upper parts relate to present geometry). High finite strain intensity correlates with low Wm and high Wm numbers near the detachment correlate with relatively weak strain intensity. Finite strain shows oblate geometries. Overall, our data indicate vertical and possibly temporal variations in deformation of the SSZ. Most AFT ages cluster around 85–75 Ma. We interpret the AFT ages to reflect the final stages of continental break-up just before and possibly during the initiation of sea-floor spreading between New Zealand and Antarctica. Highlights: Quantitative assessment of shear zone deformation in a major crustal-scale extensional shear zone in a poorly studied region. Structural, strain and vorticity data demonstrate pronounced vertical changes in the kinematics of the studied shear zone. Our data allow a new look on the tectonic evolution of the Sisters shear zone in Stewart Island, New Zealand.